Allelic variation in two distinct Pseudomonas syringae flagellin epitopes modulates the strength of plant immune responses but not bacterial motility. Issue 3 (19th July 2013) - Clarke, Christopher R.; Chinchilla, Delphine; Hind, Sarah R.; Taguchi, Fumiko; Miki, Ryuji; Ichinose, Yuki; Martin, Gregory B.; Leman, Scotland; Felix, Georg; Vinatzer, Boris A.
Summary The bacterial flagellin (FliC) epitopes flg22 and flgII‐28 are microbe‐associated molecular patterns (MAMPs). Although flg22 is recognized by many plant species via the pattern recognition receptor FLS2, neither the flgII‐28 receptor nor the extent of flgII‐28 recognition by different plant families is known. Here, we tested the significance of flgII‐28 as a MAMP and the importance of allelic diversity in flg22 and flgII‐28 in plant–pathogen interactions using purified peptides and a Pseudomonas syringae ∆fliC mutant complemented with different fliC alleles. The plant genotype and allelic diversity in flg22 and flgII‐28 were found to significantly affect the plant immune response, but not bacterial motility. The recognition of flgII‐28 is restricted to a number of solanaceous species. Although the flgII‐28 peptide does not trigger any immune response in Arabidopsis, mutations in both flg22 and flgII‐28 have FLS2‐dependent effects on virulence. However, the expression of a tomato allele of FLS2 does not confer to Nicotiana benthamiana the ability to detect flgII‐28, and tomato plants silenced for FLS2 are not altered in flgII‐28 recognition. Therefore, MAMP diversification is an effective pathogen virulence strategy, and flgII‐28 appears to be perceived by an as yet unidentified receptor in the Solanaceae, although it has an FLS2‐dependent virulence effect in Arabidopsis.